Blending Perceptual and Social Information to Guide Psychomotor Behaviour: A Study of Ghanaian and Ghanaian-American Infants - Ntim, Stephen (International Journal of Psychology, 2025)
Purpose: This study examined how mothers from two different geopolitical areas having the same cultural roots blended perceptual and social information to coax infants’ psychomotor behaviour to learn how to walk. It emphasizes how culture and acculturation (migration) shape maternal social information and their behavioral outcomes to entice infants to learn how to walk. Methodology: This research is observational quantitative. It collected and analyzed data, such as maternal coaxing of infants to walk, infants’ psychomotor decisions, infants’ perceptual exploration such as crawling or sitting down, infants facial and vocal expressions. Findings: On maternal coaxing messages to induce infants to walk, with agreed baseline of 99.5% of trials, indigenous Ghanaian mothers, scored 95%, while the Ghanaian mothers living in New York scored 89.55%. Infants’ psychomotor decisions to reciprocate maternal coaxing to walk were 180 seconds individually for four of the Ghanaian infants, while three of the infants from New York-based mothers scored 180, 178 and 174 seconds respectively. Infants’ facial expression, such as laughing and babbling, the two groups diverged significantly on a benchmark of 91.3 %. Crying and facial frowning were found to be high among Ghanaian-American infants’: Ghanaian infants scored 40 percent (37.24), while Ghanaian-Americans infants scored 60 percent (55.86). These data were interpreted to mean that even though, the two groups of mothers were both Ghanaians culturally, yet the contexts of maternal expressions to coax infants to walk varied significantly. This suggests that infants’ executive function, as well as effortful psychomotor control, do not only depend on mothers deliberate coaxing methods, they also vary both across cultures, and more significantly within cultures as a result of the impact of migration. Unique Contribution to Theory, Practice and Policy: This study underscores how critical it is to understand the process of acculturation as key to migrants’ psychological adaptation to the new culture. At both group and individual levels, acculturation often influences changes to migrants’ home culture and their indigenous social practices as they become introduced to the overarching culture of destination, highlighting the need for a culture-sensitive, Childhood Education for immigrant children as they migrate from L1 to L2.